2023
DOI: 10.1161/jaha.122.028146
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Kidney Tubular Function Deteriorate While Those of Kidney Tubule Health Improve in Primary Aldosteronism After Targeted Treatments

Vin‐Cent Wu,
Chieh‐Kai Chan,
Jeff S. Chueh
et al.

Abstract: Background Targeted treatment with mineralocorticoid receptor antagonists (MRAs) or adrenalectomy in patients with primary aldosteronism (PA) causes a decline in estimated glomerular filtration rate; however, the associated simultaneous changes in biomarkers of kidney tubule health still remain unclear. Methods and Results We matched 104 patients with newly diagnosed unilateral PA who underwent adrenalectomy with 104 patients with unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
3
0
2
Order By: Relevance
“…Regarding their suggestion for a more robust ANOVA analysis, via including patient age stratification, we are in full agreement [3]. Stratifying eGFR-dip cohorts by age promises to offer a refined perspective on risk assessment.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Regarding their suggestion for a more robust ANOVA analysis, via including patient age stratification, we are in full agreement [3]. Stratifying eGFR-dip cohorts by age promises to offer a refined perspective on risk assessment.…”
supporting
confidence: 62%
“…Robertson et al [2] demonstrated that acute caffeine consumption increased serum renin levels significantly, which would cause an increase in downstream plasma aldosterone concentrations. In addition, a large body of research demonstrated that salt intake has an inverse relationship with renin production/RAAS activation, though the exact mechanism remains unknown [3].…”
mentioning
confidence: 99%
“…In Australia and most other countries, spironolactone is commonly used as first-line therapy. An initial decline in renal function, as reflected by creatinine-based eGFR, can be observed following MRA or surgical treatment of PA because of correction of aldosterone-mediated glomerular hyperfiltration, which unmasks underlying renal dysfunction [ 55 ]. Reassuringly, the drop in eGFR does not reflect intrinsic damage to the renal tubules as biomarkers of renal tubular health are restored following targeted treatment [ 55 ] and a larger acute fall in eGFR in this setting has been associated with less decline in the longer term [ 56 ].…”
Section: Case 4 Discussion: Key Aspects In Monitoring the Medical Tre...mentioning
confidence: 99%
“…Підозра на ПГА виникає у випадку стійкого поєднання АГ із зумовленим гіпокаліємією різного ступеня вираженості специфічним нейром'язовим синдромом (оніміння, слабкість у м'язах кінцівок, втомлюваність, судоми, парестезії), а також не властивим для банальної АГ високим ризиком швидкого погіршення ниркової функції та розвитку хронічної хвороби нирок [4]. Окрім того, імовірність ПГА підвищує незадовільній контроль АТ стандартною комбінацією засобів фармакотерапії, неочікуваний позитивний терапевтичний ефект антагоністів мінералокортикоїдних рецепторів, АГ у молодих, а також сімейний анамнез ранньої АГ або інсульту у молодому віці, пароксизмальний перебіг АГ [5].…”
Section: вступunclassified
“…Більшість авторів відзначають наявність неспецифічних змін, характерних для АГ (артеріолосклеротичний нефросклероз) [17]. Описують специфічні для ПГА зміни -«гіпокаліємічну нирку» (пошкодження епітелію канальців нирки внаслідок гіпокаліємії та метаболічного алкалозу, що призводить до запалення з імунним компонентом і склерозом інтерстицію) [4]. Треба зазначити, що ураження нирок при ПГА, а по суті, розвиток вторинної нефрогенної АГ розглядається як одна з причин збереження АГ після видалення АПА.…”
Section: рисунок 1 кт заочеревинного простору стрілкою позначено ново...unclassified